تكاليف إرسال التحويلات المالية للمهاجرين في العالم أسبابها وطرق خفضها - دراسة حالة إقليم إفريقيا جنوب الصحراء الكبرى: The costs for sending remittances in the world Causes and ways to reduce it - Case Study of Sub-Saharan AFRICA- - نادية سوداني, (Journal of North African Economies, 2025)
In This study, we aim to indentify the different concepts of remittances, The costs of sending remittances, And the the transfer channels in sub-Saharan Africa, The development of these transfers in the worl, In sub-Saharan Africa, The average cost of sending is 9.3% of the amount sent, These countries have undertaken several initiatives to reduce shipping costs. The main results of this study are the: remittances are one of the source of development finance in which the economies of many countries have relied on as a source of economic development and has seen significant growth in the immigrant remittances, Money transfers (family remittances) contribute to the national economie development through several channels, The Corona crisis had impact on the development of migrant remittances in the world , and Increasing shipping costs. Sub-Saharan Africa is one of the countries most affected by the crisis.